Role of weedicides for weed management and improvement in production of berseem (Trifolium alexandrinum L.) fodder - Gondal, M. R.; Rizvi, S. A.; Naseem, W.; Khan, A.; Hayat, S.; Mustafa, S.; Arif, M.; Basit, A.; Salim, J. (International Journal of Agricultural Technology, 2021)
Berseem (Trifolium alexandrinum L.) is an important fodder crop used for feeding cattle across the globe but in Pakistan heavy weeds infestation hampers its production. The most prominent weeds namely Trianthema partulacastrum L. and Digera muricata L. deteriorate the quality and diminish the quantity of its production. Implication of weedicides for weeds management, improvement in fodder and crude protein yield were investigated. Four weedicides namely, Connect (Atrazine), Panida Grande (Pendimethalin), Dual Gold (S-metolachlor), and Primextra Gold (S-metolachlor + Atrazine) were tested at its four application times i.e., pre-sowing incorporation (0, 2, 4 days before sowing) and pre-emergence (just after sowing). Results revealed that Pendimethalin herbicide showed the best performance amongst all weedicides when used 4 days before sowing, indicating 94.73 % efficiency of weed control and produced maximum fodder yield (108.63 t ha-1), dry matter yield (14.72 t ha-1) and crude protein yield (2.92 t ha-1). Thus, it was concluded that Pendimethalin @ 2.5 L ha-1 should be applied at 4 days before sowing for effective control of all types of weeds considered under the current study and to improve the quantity and quality of berseem. Economic analysis showed a maximum benefit-cost ratio of 1.89 for treatments where Pendimethalin herbicide was applied @2.5 liter ha-1 four days before sowing